2004
DOI: 10.1038/sj.npp.1300607
|View full text |Cite
|
Sign up to set email alerts
|

Release of Oxytocin in the Rat Central Amygdala Modulates Stress-Coping Behavior and the Release of Excitatory Amino Acids

Abstract: Previous experiments have indicated that the release of oxytocin (OXT) occurs in various hypothalamic and extrahypothalamic brain areas. In the present study, we investigated in male rats whether swim stress triggers the release of OXT in the central amygdala (CeA), a key area in processing emotions and stress responses. Further, we examined the physiological significance of OXT released within the CeA for behavioral responses during forced swimming as well as effects on the local release of selected amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(128 citation statements)
references
References 59 publications
4
121
1
2
Order By: Relevance
“…Here evidence is reported of a brain system which, through modulation of GABA in the amygdala prefrontal cortical 5-HT, controls behavioral responses to stressful experiences sustaining immobility in the forced swimming paradigm that models depressive-like outcomes in rodents (Ebner et al, 2005(Ebner et al, , 2008Singewald et al, 2011). It was first demonstrated that, in mice, a stressful experience such as restraint induces a time-dependent increase of 5-HT output in the mpFC and of GABA in the BLA, in agreement with previous reports (Reznikov et al, 2009;Pascucci et al, 2009), and that selective depletion of cortical 5-HT canceled out these stress-induced responses, thus pointing to a controlling role of GABAergic transmission in amygdala by prefrontal 5-HT during stress.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Here evidence is reported of a brain system which, through modulation of GABA in the amygdala prefrontal cortical 5-HT, controls behavioral responses to stressful experiences sustaining immobility in the forced swimming paradigm that models depressive-like outcomes in rodents (Ebner et al, 2005(Ebner et al, , 2008Singewald et al, 2011). It was first demonstrated that, in mice, a stressful experience such as restraint induces a time-dependent increase of 5-HT output in the mpFC and of GABA in the BLA, in agreement with previous reports (Reznikov et al, 2009;Pascucci et al, 2009), and that selective depletion of cortical 5-HT canceled out these stress-induced responses, thus pointing to a controlling role of GABAergic transmission in amygdala by prefrontal 5-HT during stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although depression is seen largely as a dysfunction in monoamine neurotransmission and all antidepressant strategies focus largely on monoamines, strong clinical and preclinical evidence implicates dysfunction of the GABAergic system in depression (Krystal et al, 2002). In rodents, the amygdala has been shown to be involved in depressive-like behavior in the FST, at least in part through GABA release (Ebner et al, 2005;Briones-Aranda et al, 2005). Different studies described antidepressant effects of the GABAb receptor agonist baclofen in FST (Cryan and Kaupmann, 2005), conceivably through presynaptic GABAb receptor activation leading to decrease of GABA release (Rea et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations